Employing human resources at the Algerian University Policy, procedures, and impact of the organizational culture - Arioua, Nesma; Benyamina, Said (Technium Social Sciences Journal, 2022)
Giving the increased awareness of the importance of human intellectual capital for institutions of higher education in particular and national development in general, organizational and labor theorists and intellectuals have paid great attention to the standards and foundations to be followed in order to attract and select the most efficient and worthy human resource for positions commensurate with their abilities, qualifications, and competencies. This attention is noticeable at the constitutional and legal levels. Algeria is one of the countries whose constitution states that public service is a right of all citizens to be exercised in accordance with the principles of justice and equality. This has been reflected in all the legal and regulatory provisions relating to public employment, particularly in Algeria’s higher education and scientific research sector. These provisions have ensured this right while prioritizing qualified human resources, which constitute an implicit case of the recruitment process’s role in selecting the most efficient, effective, and worthy human capital (faculty members) at the level of higher education institutions.